Heritage Keepers: The Perils in Textile Conservation - Pinheiro, Ana Catarina (2022)
One of the most frequent professional afflictions in Conservators-Restorers is the onset of work-related musculoskeletal disorders (WMSDs). The conservation of textiles is recognizably vulnerable to these problems. However, the assessments of the ergonomic conditions for these workers are rare or even non-existing. The present study focuses on a group of conservators-restorers of textiles and relies on the use of a Nordic Questionnaire for musculoskeletal disorders coupled with a Quick Exposure Check for the task of consolidation on a horizontal table to determine the severity and exposure levels to WMSDs. All surveyed workers reported numbness, pain or discomfort in the last 12 months for the neck region, while 67% reported the same afflictions for the back, shoulders/arms and hands/wrist. In the same time period, half of the workers used pain relievers in order to maintain their professional activity. For the textile consolidation task, the neck and back areas showed high and very high levels of exposure, respectively, and the results place these workers at a high-risk for WMSDs due to cumulative stress. Mitigation strategies are proposed but these should be paired with professional counseling. Although preliminary, this study is the first of its kind to assess the ergonomic impact of the profession in Portugal and presents a methodology that can be used to perform similar evaluations in other workplaces and/or other specialties in the Conservation and Restoration sphere, both nationally and internationally